2009
DOI: 10.1002/for.1166
|View full text |Cite
|
Sign up to set email alerts
|

Estimating overnight de facto population by forecasting symptomatic variables: an integrated framework

Abstract: In spite of the importance that measurements of temporary (de facto) populations have for public sector planning of services and infrastructures and for private fi rms' location purposes, no well-established framework exists in the literature showing how to systematically perform such estimates. As a fi rst step to overcoming the conceptual and practical diffi culties surrounding the estimation of de facto population, this paper relies on forecasting symptomatic variables to integrate existing direct and indir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Large samples are needed for robust estimates of the timing, location, and purpose of temporary moves. Symptomatic indicators such as water consumption, retail sales, and accommodation occupancy have been used as an alternative to survey data to estimate seasonal variation in population numbers in selected localities (Krug, ; Rigall‐I‐Torrent, ), but these data reflect changes in the stock of visitors, rather than the inward and outward flows. In recent years, analysts have also made use of mobile phone data to track population movements and estimate seasonal shifts in populations (Ahas et al ., ; Silm and Ahas, ).…”
Section: Datamentioning
confidence: 99%
“…Large samples are needed for robust estimates of the timing, location, and purpose of temporary moves. Symptomatic indicators such as water consumption, retail sales, and accommodation occupancy have been used as an alternative to survey data to estimate seasonal variation in population numbers in selected localities (Krug, ; Rigall‐I‐Torrent, ), but these data reflect changes in the stock of visitors, rather than the inward and outward flows. In recent years, analysts have also made use of mobile phone data to track population movements and estimate seasonal shifts in populations (Ahas et al ., ; Silm and Ahas, ).…”
Section: Datamentioning
confidence: 99%
“…It has been suggested that the notions of home, place of residence, migration, and population do not suffice to understand increasingly diverse forms of mobilities, often related to tourism and multiple residence (McIntyre et al 2006). Attempts to acknowledge temporary mobility in population measures have been mainly made within tourism studies (Terrier 2006;Rigall-i-Torrent 2010). Müller and Hall (2003) estimated seasonal population redistribution related to second home use in Sweden.…”
Section: Introductionmentioning
confidence: 99%
“…Symptomatic data sets such as water or electricity usage, while providing fine-grained temporal data, are often spatially discrete and provide little or no information on the composition of populations. Furthermore, these data sets are often non-stationary over space and time as other factors such as climate and seasonal effects impact usage [ 11 ]. Symptomatic data are usually collected by companies or institutions for specific geographical areas, making it difficult to consolidate them into larger national datasets.…”
Section: Introductionmentioning
confidence: 99%